Welfare in nile tilapia production: Dorsal fin erection as a visual indicator for insensibility - Camargo-Dos-santos, Bruno [UNESP]; Carlos, Clarissa Lerois [UNESP]; Favero-Neto, João [UNESP]; Alves, Nina Pacheco Capelini [UNESP]; Gonçalves, Bruno Bastos; Giaquinto, Percília Cardoso [UNESP] (MDPI, 2021)
In aquaculture, to ensure animal welfare in pre-slaughter and slaughter stages, it is fundamental that fish are insensible. A method for evaluating fish insensibility is based on visual sensibility indicators (VSI) assessment (i.e., self-initiated behavior, responses to stimuli and reflexes). However, many stimuli used to assess fish responses are painful. Therefore, this study verifies whether the presence/absence of a dorsal fin erection (DFE) response can be used as a painless VSI in Nile tilapia (Oreochromis niloticus). Three stunning protocols were applied to fish: benzocaine anesthesia (40 mg/L and 80 mg/L), ice water immersion (0–1, 2–3 and 5–6 °C) and CO2 stunning. After these stunning methods were applied in fish, the time of loss and return of DFE was observed, along with the vestibulo-ocular reflex (VOR). All fish stunned using benzocaine and ice water immersion lose both VSIs, while 95% of fish stunned using CO2 lose these VSIs. In all treatments, DFEs return quicker than VOR. Therefore, DFE can be used as a VSI in Nile tilapia, which is simple for producers to assess and does not require a painful stimulus. However, the DFE alone does not totally ensure fish insensibility and must be used together with other well-established VSIs at fish farms.
Keywords: Animal welfare; Aquaculture; Fish stunning; Pre-slaughter; Sensibility state